INTEGRASI AGAMA DAN SAINS DALAM PERSPEKTIF NAQUIB AL-ATTAS - Nurry Marfu'ah; Eva Dewi; Sari Madani Rambe (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Nowadays, the relationship between religion and science is always discussed in an interesting way. Science knowledge in human life has experienced significant development and change. But in terms of religion, many still think of it as a tradition from previous people that is only followed casually. In the 20th century, science and technology are currently experiencing very rapid development. Science and technology in the West, such as computers, laptops, and mobile phones, experienced rapid progress in the 17th-18th centuries, starting from the scientific revolution against religious authority in the 12th-13th centuries. Since that century science has not followed religious rules and separated itself from religious authority. Syed Muhammad Naquib al-Attas is a very influential figure in the world of education, especially in the fields of religion and science. Al-Attas is famous for the idea of Integration of Religion and Science which he applied in the Islamization of Science. The purpose of this study is to find out more about al-Attas' integration in integrating religion and science. Data collection techniques were obtained from the library in the form of books, journals, and relevant conference proceedings, especially those related to the ideas of Naquib Al-Attas, using qualitative methodology. The results concluded that al-Attas wanted to free human thought from belief in magic, mythology, animism and traditional culture that deviated from Islam, as well as secular control over reason and language known as the concept of Islamization of Science. There are two important steps in Islamizing science, namely dewesternization and integration.